An exploration of the work experiences of taxi drivers in Cape Town: A study of Delft and Khayelitsha - Kom, Milisa (Department of Social Development, 2025)
Studies have outlined both the good and the bad sides of the taxi industry, pointing out that while it makes a positive economic contribution to the country through employment generation, the industry is beset by challenges. Among these are reckless driving, the use of unroadworthy vehicles, and persistent violence and turf wars that lead to widespread animosity and loss of life. Although there are many minibus taxi drivers in South Africa, little is known about the experiences of these employees, as most of the information provided by existing studies is based on government records rather than on personal interviews with taxi drivers. The aim of this study is to explore the work experiences of minibus taxi drivers in the Cape Town area, with a focus on Delft and Khayelitsha. The study sought to gain insight on the work experiences of minibus taxi drivers, looking at their health, social and family life, challenges, and the changes they wish to see in the industry. Methodologically, this aim was achieved through a qualitative study that adopted a phenomenological approach, in which 15 minibus taxi drivers in Cape Town, specifically Khayelitsha and Delft, were interviewed. The sample was purposively selected based on certain criteria and was conducted at Site C taxi rank in Khayelitsha, as well as the section of Delft taxi rank for the Palam and Mitchells Plain routes. Data collected from the participants was analysed using two theoretical frameworks: Social Exclusion Theory and Crenshaw's Intersectionality Theory. The results of this study have shown that the taxi driving job involves negative effects on the health and wellbeing of minibus taxi drivers, resulting in their use of poor coping strategies such as unhealthy eating and substance abuse. In addition, the taxi driving job was found to result in a deterioration of social and family life as a result of long working hours. The job has benefits such as providing relatively easy, low skilled employment and access to regular cash. Lastly, the findings show that minibus taxi drivers are faced with challenges such as exploitative working conditions, poor pay, and exposure to violence, prompting many to seek better working environments and growth. The findings of this study could inform the development of better employment policies for workers in the taxi industry and serve a guide to formalising processes in the taxi industry.